Analysis of Value Co-Creation in the Subscription-Based Digital Economy - Yudikasih Halawa; Sariyoke Shintaruni (JENOVA : Journal of Economics, Finance, Accounting, and Organizational Advancement, 2025)
This study examines the role of value co-creation in the subscription-based digital economy, particularly in strengthening customer retention and supporting long-term monetization through add-on bundling strategies. The study focuses on how customer participation, feedback, personalization, and platform interaction contribute to retention intention, Average Revenue Per User (ARPU), and churn reduction. A mixed-method approach was applied by combining survey data from 1,000 users of digital subscription services, including Netflix, Spotify, and local SaaS platforms, with qualitative insights from Product Managers. Quantitative data were analyzed using multiple linear regression with robust standard errors and logistic regression as a robustness test. The findings show that value co-creation has a positive and significant effect on customer retention (β = 0.459; p < 0.001) and reduces the probability of 60-day churn by 14.7 percentage points. However, its direct effect on monthly ARPU is not statistically significant (β = IDR 216; p = 0.706), indicating that co-creation primarily operates through the retention channel rather than direct revenue expansion. The qualitative findings further suggest that effective add-on bundling should emphasize flexibility, personalization, and complementarity. This study contributes to Service-Dominant Logic by showing that co-creation functions as a strategic retention mechanism in digital subscription business models.